2009
DOI: 10.1111/j.1528-1167.2008.01787.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral frontoparietal polymicrogyria, Lennox‐Gastaut syndrome, and GPR56 gene mutations

Abstract: Summary Purpose:  Bilateral frontoparietal polymicrogyria (BFPP) has been reported in sporadic patients and in recessive pedigrees. Eleven mutations in GPR56, a gene encoding an evolutionarily dynamic G‐protein–coupled receptor, have been identified in 29 patients from 18 families. The clinical features of BFPP include severe mental retardation, motor and language impairment, and epilepsy. No detailed description of the epilepsy is available for the patients reported to date. We report three consanguineous fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 41 publications
4
53
0
Order By: Relevance
“…Even though many genes associated with brain malformations have been identified, the precise embryopathologic mechanisms are far from clear. Parrini et al 44 have recently shown that identical mutations in the GPR56 gene cause frontal polymicrogyria in different areas of the frontal lobes, and they do not fully understand why. Genetic polymicrogyrias, such as those associated with 22q11.2 deletions, 45 often have asymmetric involvement of the cerebral hemispheres, but it is not clear why that is the case.…”
Section: Discussionmentioning
confidence: 99%
“…Even though many genes associated with brain malformations have been identified, the precise embryopathologic mechanisms are far from clear. Parrini et al 44 have recently shown that identical mutations in the GPR56 gene cause frontal polymicrogyria in different areas of the frontal lobes, and they do not fully understand why. Genetic polymicrogyrias, such as those associated with 22q11.2 deletions, 45 often have asymmetric involvement of the cerebral hemispheres, but it is not clear why that is the case.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may still elicit GGE [Parrini et al, 2009]. Patient 3 had maternal family members with a diagnosis of JME (but not 22q11DS), suggesting a familial GGE disorder independent of 22q11DS.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence in siblings is extremely rare and has been reported in a family with bilateral frontoparietal polymicrogyria due to GPR56 mutations [94]. Recently Lawrence et al reported a novel DXC mutation in a family with three siblings affected by LGS and anterior pachygyria [95].…”
Section: Introductionmentioning
confidence: 99%